KARAKTERISTIK KOMPONEN ABIOTIK ANOA (Bubalus sp) HABITAT DALAM HUTAN PENDIDIKAN TADULAKO UNIVERSITAS KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Allo, Rimba Putra Ampang; Sudhartono, Arief; Labiro, Elhayat (Universitas Tadulako, 2018)
Education Forest of Tadulako University located in Central Sulawesi that has Â± 6.000 Ha largeÂ is one of habitat of Sulawesi endemic and rare animal, anoa. The research aimed to find out the characteristic of abiotic component of anoa (Bubalus sp) habitat in Education Forest of Tadulako University area. The conservation effort toward the rare animals necessary to be done in order to keep the preservation and the balance of ecosystem. The research applied survey method based the track and feces of anoa then the spot of anoa habitat determined. To take the sample of abiotic component of anoa habitat was done purposively where the mud hole found, the place to find food, drink, doing activity and taking rest of anoa. The research focused on abiotic components of anoa habitat such as , soil, water, temperature and air humidity. The information about soil, water, temperature, and air humidity of anoa habitat were expected to make the preservation activities of the wildlife easier. Based on the result of the research and laboratory analysis, five spots of observation of anoa; places for doing activities, for resting, for finding food, drinking and wallowing in the mud hole, the air temperature was about 190 C - 230 C and the air humidity was about 80,5% - 84,2%, turbiditas of dringking water was about 0,07 FAU, water of mud hole 0,22 FAU, water salinity and mud hole was 0,00 ppt, pH of drinking water was 6,75, water of mud hole was 5,66, pH of soil was about 4,38 - 5,68 and it dominated by clay soil, the height was about 690 - 712 mdplÂ generally had slope slightly topography.Keywords : Anoa, Bubalus sp, Habitat, Education Fores